2009
DOI: 10.1136/hrt.2009.178392
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of molecular forms of plasma brain natriuretic peptide in heart failure--different proBNP-108 to BNP-32 ratios in atrial and ventricular overload

Abstract: These results suggest that BNP-32 and proBNP-108 is increased in HF and that the proBNP/total BNP ratio increases in association with pathophysiological conditions such as ventricular overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 27 publications
2
43
0
2
Order By: Relevance
“…Plasma BNP levels were measured using specific immunoradiometric assay for human BNP (TOSOH Corp, Tokyo, Japan) [23]. Minimal detectable quantity of human BNP was 2.0 pg/mL.…”
Section: Hormonal and Biochemical Analysismentioning
confidence: 99%
“…Plasma BNP levels were measured using specific immunoradiometric assay for human BNP (TOSOH Corp, Tokyo, Japan) [23]. Minimal detectable quantity of human BNP was 2.0 pg/mL.…”
Section: Hormonal and Biochemical Analysismentioning
confidence: 99%
“…Nishikimi et al showed that proBNP-108 was the major molecular form in ventricular tissue, and BNP-32 was the major molecular form in atrial tissue. 31 ProBNP-108 measurement may solve the mystery of the irrelevant BNP levels in the present study. Finally, the proportion of patients with MMPs among all the subjects was low in the present study.…”
Section: Irrelevant Bnp Level In Mitral Prosthesis Patientsmentioning
confidence: 97%
“…Доказано, что НУП участвуют в процессах торможения роста и пролиферации кардиомиоцитов, что снижает компенсаторную гипертрофию миокарда [130]. Продукты активации проНУП, особенно проBNP, используются в диагностике [132]. Уровень proBNP возрастает в крови больных с острым коронарным синдромом, являясь важным свидетельством развития сердечной недостаточности, а степень увеличения его концентрации в крови этих пациентов определяет прогноз заболевания в отдаленные сроки [132,133].…”
Section: активация натрийуретического пептида с-типаunclassified
“…Продукты активации проНУП, особенно проBNP, используются в диагностике [132]. Уровень proBNP возрастает в крови больных с острым коронарным синдромом, являясь важным свидетельством развития сердечной недостаточности, а степень увеличения его концентрации в крови этих пациентов определяет прогноз заболевания в отдаленные сроки [132,133]. -dependent endopeptidases of the subtilisin family, also known as proprotein convertase (PC).…”
Section: активация натрийуретического пептида с-типаunclassified